The Lived Experience of Mothers on the Verge of Separation: A Case Study of Isfahan City - Ghanbarian , Sepideh; Faramarzi, Salar; Tabrizi , Mehdi (Applied Family Therapy Journal (AFTJ), 2024)
Objective: The present research aimed to study the lived experience of mothers on the verge of separation and to explore the phenomenon of separation and divorce from their perspective.Method: It was a qualitative study with a phenomenological method among mothers on the verge of separation in Isfahan city. Semi-structured interviews were used for data collection in this research. Participants included 15 mothers on the verge of separation in Isfahan city in the year 2021, using purposive sampling, and the operations of data collection and analysis were conducted simultaneously.Findings: According to the analysis and the extracted main and sub-categories, the story of mothers on the verge of separation can be narrated within 5 overarching themes. The results of this research, from among 180 thematic sentences from the statements of mothers on the verge of separation about their experiences, eventually classified 5 overarching themes and 15 organizing themes that form the network of themes. The overarching and organizing themes in this research include communication problems (relationships with children, relationships with spouses), parenting (children's financial problems, defective parenting style, child management), emotional and behavioral (emotional and behavioral problems of parents, emotional and behavioral problems of children), psychological, social, and economic support (family, lack of counseling, economic) and exacerbating factors (extramarital affairs, addiction, previous divorce experience, mental disorders, sexual dysfunction).Conclusions: The results showed that mothers on the verge of separation experience emotions that can affect their well-being and mental health. The findings highlight the necessity for psychologists and social workers to deeply understand the lived experiences of these individuals and to offer therapeutic interventions based on the themes emerged from the current study, focusing on improving their emotional state.